2018
DOI: 10.1093/ofid/ofy216
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Kidney Disease and Poor Diagnostic Accuracy of Dipstick Proteinuria in Human Immunodeficiency Virus-Infected Individuals: A Multicenter Study in Japan

Abstract: BackgroundChronic kidney disease (CKD) has become one of the common comorbid conditions affecting the human immunodeficiency virus (HIV) population. Human immunodeficiency virus-infected individuals are at increased risk of developing CKD, and they are likely to experience faster progression of renal dysfunction compared with HIV-uninfected individuals. Albuminuria represents not only kidney damage but also manifests metabolic syndrome and vascular dysfunction.MethodsWe conducted a multicenter, cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
1
8
0
2
Order By: Relevance
“…As the proportion of patients who had received an annual S-Cr or FPG test was relatively low, especially in LMIC, it is possible that our findings are not an accurate estimate of the prevalence of CKD and diabetes in the study population. Still, regardless of country income, the prevalence we observed for these conditions is largely in the range of what has been found in other studies from the Asian region, which have reported CKD in 7% to 20% and diabetes in 5% to 27% of PLHIV [28][29][30][31][32][33][34]. Furthermore, the finding that the prevalence of both of these NCDs was higher in LMIC than in HIC reflects what has been observed in the general population [35,36].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As the proportion of patients who had received an annual S-Cr or FPG test was relatively low, especially in LMIC, it is possible that our findings are not an accurate estimate of the prevalence of CKD and diabetes in the study population. Still, regardless of country income, the prevalence we observed for these conditions is largely in the range of what has been found in other studies from the Asian region, which have reported CKD in 7% to 20% and diabetes in 5% to 27% of PLHIV [28][29][30][31][32][33][34]. Furthermore, the finding that the prevalence of both of these NCDs was higher in LMIC than in HIC reflects what has been observed in the general population [35,36].…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, definitions for CKD and diabetes differ across literature. Various markers have been used to diagnose the conditions and often diagnosis is confirmed by a second assessment taken at a later point in time [21,[28][29][30]. We based the prevalence of CKD and diabetes on single assessments of S-Cr and FPG, respectively, because of the low number of patients with multiple assessments a year.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous report [30], the positive rate of proteinuria by the dipstick method (≥ 1+) in HIVinfected patients was 8.9% in 2135 HIV patients. On the other hand, in a survey of 332,174 people in the Japanese general population (mean age 63.6 years, 14.5% with stage ≥ 3 CKD), proteinuria was observed in 5.4% [38].…”
Section: High Prevalence Of Proteinuria In Hiv-infected Patientsmentioning
confidence: 90%
“…We first reported prevalence of CKD of stages 1-5 and stages 3-5 as 14.9-87.8% and 3.5-16.2%, respectively, in Japan [23,24,28,29]; however, there remained the possibility of institutional and methodological bias, as they were the results in HIV-infected patients at a single or two institutions. To determine a more actual prevalence of CKD in HIV-infected patients in Japan, a cross-sectional study was conducted in 2135 HIVinfected individuals (2008 males and 127 females, mean age 44.4 ± 11.5 years) at 5 institutions in Tokyo between April 2012 and March 2013 [30]. In this study, the prevalence of CKD stages 1-5 and stages 3-5 are 15.8% and 9.6%, respectively, according to the traditional staging system, and the prevalence of proteinuria detected by the dipstick method (≥ 1+) was 8.9%.…”
Section: Characteristics Of Ckd and Esrd Among Hivinfected Patients Imentioning
confidence: 99%
“…In patients infected by HIV, kidney disease has become The prevalence of HIV-associated chronic kidney disease varies geographically and depends on the definition used 12 . In addition to having a higher risk of kidney disease, individuals infected by the virus also present greater speed of progression of renal dysfunction compared to non-infected individuals 13 .…”
Section: Introductionmentioning
confidence: 99%